The Canadian feminists’ translation project: between feminism and postcolonialism - Bertacco, Simona (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
In this article, Canada and Quebec are taken as case studies providing some interesting examples of inter-linguistic but intra-national translation, texts presenting features which can be addressed under the broad rubric of postcolonialism, especially as far as the power relations between the English and French languages in Canada are concerned. As a matter of fact, the socalled politics of translation appear only too clearly if we analyze the texts which are translated across the border between Canada and Quebec. Within this context, there has been a group of writers and scholars from both linguistic areas who have been willing to meet on a different ground – the ground of feminist writing and translation. Among the most important women in the group, Barbara Godard and Sherry Simon, as well as writers such as Nicole Brossard and Daphne Marlatt, deserve to be mentioned for the visibility their works have achieved in the past decades, and for the issues they raise.